2005
DOI: 10.1080/03610730590948195
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Curve Model of Learning Acquisition among Cognitively Normal Older Adults

Abstract: Address correspondence to Richard N. Jones, ScD, Senior Research Associate, Hebrew Rehabilitation Center for Aged, Research and Training Institute, 1200 Centre Street, Boston, MA 02131, USA. jones@mail.hrca.harvard.edu. A preliminary version of this study was presented at the 54th Annual Scientific Meeting of the Gerontological Society of America, November 16, 2001, Chicago, Illinois. The ACTIVE study (Advanced Cognitive Training for Independent and Vital Elderly) is a multisite collaborative cognitive interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 43 publications
6
45
0
1
Order By: Relevance
“…Several researchers have investigated the relation of growth curve parameters, i.e., baseline performance and performance growth, to intelligence and other predictors to investigate determinants of individual differences in skill-acquisition (e.g., Jones et al, 2005;Voelkle, Wittmann, & Ackerman, 2006) or the specificity of learning ability with respect to task material (e.g., Zhang, Davis, Salthouse, & Tucker-Drob, 2007). These studies provide some support for Ackerman's theory.…”
Section: The Relation Of Intelligence and Other Abilities To Task Permentioning
confidence: 94%
See 2 more Smart Citations
“…Several researchers have investigated the relation of growth curve parameters, i.e., baseline performance and performance growth, to intelligence and other predictors to investigate determinants of individual differences in skill-acquisition (e.g., Jones et al, 2005;Voelkle, Wittmann, & Ackerman, 2006) or the specificity of learning ability with respect to task material (e.g., Zhang, Davis, Salthouse, & Tucker-Drob, 2007). These studies provide some support for Ackerman's theory.…”
Section: The Relation Of Intelligence and Other Abilities To Task Permentioning
confidence: 94%
“…Baseline performance increased up to the age group 19-39 years; across older age groups there was a decrease in baseline performance. Jones et al (2005) investigated in a sample of older adults the influence of predictors on growth curve parameters when performing an auditory verbal learning test including multiple recall trials. Their study showed that baseline recall performance was significantly associated with demographic characteristics, e.g., age had a negative effect on baseline performance, but unrelated to health factors and cognitive abilities.…”
Section: The Relation Of Intelligence and Other Abilities To Task Permentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding possible mechanisms of how verbal knowledge affects individual differences in learning, there are some studies that provided evidence for a positive relation between verbal knowledge and verbal learning (Jones et al 2005;Kyllonen et al 1991;Rast 2011). Rast (2011 emphasized, in particular, the role of verbal knowledge for learning rates in old age.…”
Section: Individual Differences In Criterion-based Dropout Learning Imentioning
confidence: 99%
“…The latent deprivation index will be used as input values in an LGC model (Hamaker 2005;Jones et al 2005;Llabre et al 2004). The basic idea of growth modelling is to describe developmental trajectories over time in terms of parsimonious models.…”
Section: Structural Equation Modelling and Growth Curve Modellingmentioning
confidence: 99%